Intraspecific variation in seed germination and storage behaviour of Cordia tree species of subtropical montane forests of Argentina: Implications for ex situ conservation - Galindez, Guadalupe; Ledesma Guaraz, Tilda Teresa; Alvarez, Ana Carolina; Pastrana Ignes, Valeria Andrea; Bertuzzi, Tatiane; Lindow López, Lucía; Sühring, Silvia Susana; Ortega Baes, Francisco Pablo (Elsevier, 2019)
Cordia americana, C. saccelia and C. trichotoma are native trees of the subtropical Andean forests of Argentina. Due to their high value as a wood source, these species are under threat from the over-exploitation of their populations and from changes in land use. Knowledge of seed biology may contribute to clarifying their regeneration ecology and establishing management policies and conservation programmes. We studied seed mass, seed germination, seed desiccation tolerance and seed storage behaviour in seeds from different populations of each species. Seed mass differed among the populations of each species. For C. americana and C. saccelia, germination percentages (GP) varied among populations and light and temperature conditions. For all species and populations, GP was not affected by seed population or desiccation treatments, but the time to germination (t50) increased after drying. GP decreased and t50 increased in seeds stored with 8–10% MC at 35 °C for three months for all species and populations. Seeds stored with 8–10% MC at 20 °C and with 3–5% MC at 35 °C also showed deterioration depending on the species. Differences in germination requirements, desiccation tolerance and storage behaviour were not related to seed mass. These results indicate that (1) all Cordia species seeds show orthodox storage behaviour, (2) both moisture content and temperature are key factors in Cordia seed storage and (3) some populations within a species are more sensitive to desiccation and storage conditions than others. Thus, these species and populations could be preserved in seed banks, but the germination, desiccation and storage behaviour variability among populations must be considered before germination and storage protocols are established. This information will be very useful for designing restoration, reforestation, plant propagation and in situ and ex situ conservation programmes for these Cordia species.